Evaluating the agricultural policy in Kosovo: Lessons learnt and the pathway forward - Egzon Bajrami (Martin-Luther-Universität Halle-Wittenberg, 2024)
Agricultural extension services and direct payments are key policy instruments; yet their effectiveness is often debated. Extension services lack a demand-driven approach, neglecting farmer preferences. Similarly, the effects of direct payments, particularly coupled payments, remain unclear. Thus, this dissertation studies farmers' preferences for extension services and the impact of coupled direct payments using experimental and quasi-experimental approaches, along with ethnographic fieldwork. Results reveal a preference for extension services with more farm visits, specialized expertise, demonstrations, and ICT use. Farmers are even willing to pay for improved services. While coupled payments had no impact on productivity or incomes, they positively affected farm size. Also, environmental effects were observed through land, livestock, and chemical use. Policy implications extend beyond the study region, while also emphasizing the importance of data reliability over availability. – – Agrarberatungsdienste und Direktzahlungen sind wichtige, aber umstrittene politische Instrumente. Diesen fehlt oft eine nachfrageorientierte Methode. Außerdem bleiben die Auswirkungen von gekoppelten Zahlungen unklar. Diese Dissertation untersucht daher Präferenzen der Landwirte für Beratungsdienste und den Einfluss gekoppelter Direktzahlungen. Die Ergebnisse experimenteller, quasiexperimenteller Ansätze sowie ethnographische Feldforschung zeigen eine Präferenz der Landwirte für Beratungsdienste mit Betriebsbesuch, Fachwissen, Demonstrationen und IKT Nutzung. Landwirte sind auch bereit für verbesserte Dienstleistungen zu zahlen. Gekoppelte Zahlungen zeigten keine Auswirkungen auf die Produktivität oder das Einkommen, hatten jedoch einen positiven Einfluss auf die Betriebsgröße. Umweltauswirkungen zeigten sich in der Landnutzung, im Viehbestand und beim Einsatz von Chemikalien. Die politischen Folgen reichen über die Region hinaus und betonen zuverlässige Daten über Verfügbarkeit.
urn:nbn:de:gbv:3:4-1981185920-1183811
Keywords: 330